Assessment of Aquifer Vulnerability to Contamination in Khanyounis Governorate, Gaza Strip - Palestine, Using the DRASTIC Model within GIS Environment - Akram Al Hallaq; Basheer Abu Elaish (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This study aims to: 1) assess the vulnerability of the aquifer to contamination in Khanyounis governorate, 2) find out the groundwater vulnerable zones to contamination in the aquifer of the study area, and 3) provide a spatial analysis of the parameters and conditions under which groundwater may become contaminated by applying the DRASTIC model within GIS environment. The model uses seven environmental parameters: Depth of water table, net Recharge, Aquifer media, Soil media, Topography, Impact of vadose zone, and hydraulic Conductivity to evaluate aquifer vulnerability. Based on this model and by using ArcGIS 9.3 software, an attempt was made to create vulnerability maps for the study area. According to the DRASTIC model index and pesticide DRASTIC index, the study has shown that in the western part of the study area the vulnerability to contamination ranges between high and very high due to the shallowness of water table with moderate to high recharge potential, and permeable soils. To the east of the previous part and in the south-eastern part, vulnerability to contamination is moderate. In the central and the eastern part, vulnerability to contamination is low due to depth of water table. Vulnerability Analysis of the DRASTIC Model indicates that the highest risk of contamination of groundwater in the study area originates from the soil media. The impact of vadose zone, depth to water level, and hydraulic conductivity imply moderate risks of contamination, while net recharge, aquifer media, and topography impose a low risk of aquifer contamination. The coefficient of variation (CV) indicates that a high contribution to the variation of vulnerability index is made by the topography. Moderate contribution is made by the depth to water level, and net recharge, while impact of vadose zone, hydraulic conductivity, soil media, and Aquifer media are the least variable parameters. The low variability of the parameters implies a smaller contribution to the variation of the vulnerability index across the study area. Moreover, the "effective" weights of the DRASTIC parameters obtained in this study exhibited some deviation from that of the "theoretical" weights. Soil media and the impact of vadose zone were the most effective parameters in the vulnerability assessment because their mean "effective" weight was higher than their respective "theoretical" weight.. This explains the importance of soil media and vadose layers in the DRASTIC model. However, it is advised to get the accurate and detailed information on these two specific parameters. The GIS technique has provided efficient environment for analyses and high capabilities of handling large spatial data. Given these results, this model highlights as a tool can be used by national authorities, and decision makers especially in the agricultural areas that use chemicals and pesticides which are most likely to contaminate groundwater resources.